Activity‐Based Sensing: A Synthetic Methods Approach for Selective Molecular Imaging and Beyond. Issue 33 (23rd April 2020) - Bruemmer, Kevin J.; Crossley, Steven W. M.; Chang, Christopher J.
Abstract: Emerging from the origins of supramolecular chemistry and the development of selective chemical receptors that rely on lock‐and‐key binding, activity‐based sensing (ABS)—which utilizes molecular reactivity rather than molecular recognition for analyte detection—has rapidly grown into a distinct field to investigate the production and regulation of chemical species that mediate biological signaling and stress pathways, particularly metal ions and small molecules. Chemical reactions exploit the diverse chemical reactivity of biological species to enable the development of selective and sensitive synthetic methods to decipher their contributions within complex living environments. The broad utility of this reaction‐driven approach facilitates application to imaging platforms ranging from fluorescence, luminescence, photoacoustic, magnetic resonance, and positron emission tomography modalities. ABS methods are also being expanded to other fields, such as drug and materials discovery. Abstract : ABSolute selectivity : Stemming from supramolecular chemical receptors that rely on lock‐and‐key binding, activity‐based sensing (ABS) methods utilizing a variety of chemical reaction approaches offer the highly selective detection of small molecules and metals in biological systems. This Review discusses key design principles, reaction development, and sensing methods, and gives an outlook on this emerging field.